(untitled) (Commonwealth Journal of Local Governance, 2024)
In rural Bangladesh, local government institutions, especially union parishads, play a key role providing essential services for community development. They help connect people with primary healthcare, along with providing nutrition and water, sanitation, and hygiene (WASH) services that reduce the burden of poverty. However, most union parishad officials are not engaged in the promotion of maternal and newborn health (MNH) services in rural areas. Lack of information about their mandated role and responsibilities prevents them from providing MNH services for poor and marginalised communities. Even if they are informed, without the necessary skills to fulfil their role and responsibilities local government officials are struggling to promote quality MNH services within the public facilities in rural areas. To address this problem, Save the Children International engaged local government institutions in a systematic manner to ensure their engagement and contribution to MNH services for rural communities.